Stigmatization and discrimination towards people living with or affected by HIV/AIDS by the general public in Malaysia - Wong, L.P.; Syuhada, A.R. (2011)
Globally, HIV/AIDS-related stigma and discriminatory attitudes deter the effectiveness of HIV prevention and care programs. This study investigated the general public's perceptions about HIV/AIDS-related stigma and discrimination towards people living with or affected by HIV/AIDS in order to understand the root of HIV/AIDS-related stigma and discriminatory attitudes. Study was carried out using qualitative focus group discussions (FGD). An interview guide with semi-structured questions was used. Participants were members of the public in Malaysia. Purposive sampling was adopted for recruitment of participants. A total 14 focus group discussions (n = 74) was carried out between March and July 2008. HIV/AIDS-related stigma and discrimination towards people living with HIV/AIDS (PLWHA) was profound. Key factors affecting discriminatory attitudes included high-risk taking behavior, individuals related to stigmatized identities, sources of HIV infection, stage of the disease, and relationship with an infected person. Other factors that influence attitudes toward PLWHA include ethnicity and urban-rural locality. Malay participants were less likely than other ethnic groups to perceive no stigmatization if their spouses were HIV positive. HIV/AIDS-related stigma and discrimination were stronger among participants in rural settings. The differences indicate attitudes toward PLWHA are influenced by cultural differences.